2011
DOI: 10.1007/s00330-011-2271-7
|View full text |Cite
|
Sign up to set email alerts
|

CT image quality improvement using adaptive iterative dose reduction with wide-volume acquisition on 320-detector CT

Abstract: This study showed that Adaptive Iterative Dose Reduction (AIDR) reduces image noise. In a phantom image noise was reduced without altering spatial resolution. In patients AIDR reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(132 citation statements)
references
References 27 publications
3
127
0
2
Order By: Relevance
“…17) However, IR algorithms introduced from some vendors 17) represent new techniques designed to reduce image noise and improve image quality using low doses of radiation. [8][9][10] An in vivo study by Kurata et al revealed that Agatston scores tend to decrease as sonogram affirmed iterative reconstruction (SAFIRE) levels increase. 18) Our observation that Agatston scores tend to decrease as IR levels increase further support these conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17) However, IR algorithms introduced from some vendors 17) represent new techniques designed to reduce image noise and improve image quality using low doses of radiation. [8][9][10] An in vivo study by Kurata et al revealed that Agatston scores tend to decrease as sonogram affirmed iterative reconstruction (SAFIRE) levels increase. 18) Our observation that Agatston scores tend to decrease as IR levels increase further support these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Furthermore, some ex vivo and in vitro studies have reported no significant differences in CAC score between standard-dose FBP and low-dose IR algorithms when the CAC score is relatively high (300-700). [11][12][13] However, the effects of dose reduction and IR on CAC score remain uncertain when the CAC score is low.…”
Section: Introductionmentioning
confidence: 99%
“…CT scan conditions were 120-kV tube voltage, 450-mA tube current, 1.0 s per rotation, slice collimation of 280 3 0.5 mm and volumetric scan mode. Reconstruction conditions were a 1.0-mm slice thickness using the iterative reconstruction algorithm adaptive iterative dose reduction 3D (AIDR3D), [21][22][23] with or without SEMAR. The convolution kernel was the standard body (FC13).…”
Section: Phantom Study Data Acquisitionmentioning
confidence: 99%
“…In this work, ASIR and iDose 4 provided almost the same MTF as that of FBP, and VEO indicated a higher MTF than that of FBP. Gervaise et al [8] demonstrated MTF results of the first generation of IR developed by Toshiba Medical Systems, AIDR, measured using a phantom including a 0.28-mm tungsten wire. In the study, there was no spatial resolution difference between FBP and AIDR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some reconstruction methods that make use of the iterative reconstruction (IR) technique have been developed by major CT manufacturers, and these methods have been applied to clinical CT examinations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%